Earthquake affects subsidence in Jakarta using Sentinel-1A time series images and 2D-MSBAS method - Yusup Nur Khakim, Mokhamad; Supardi, Supardi; Tsuji, Takeshi (Vietnam Journal of Earth Sciences, 2022)
Excessive groundwater extraction has been well known as the main factor causing land subsidence in several cities in Jakarta Basin, Indonesia. This area is surrounded by active geological structures and has thick sediments. This study emphasizes the impacts of earthquakes on subsidence over Jakarta and its surroundings by using the Sentinel-1A images and 2D-MSBAS (Multidimensional Small Baseline Subset) method. Sixty-one ascending and 66 descending Sentinel-1A images were utilized to derive 121 deformation maps from 26 March 2017 to 2 July 2019 by using the 2D-MSBAS method. Linear and nonlinear displacement variations were analyzed to understand earthquake impacts on the subsidence and their seasonal characteristics. On 23 January 2018, the Mw 5.9 earthquake shaking off the coast of Java significantly affected ground surface subsidence in Jakarta. A cumulative magnitude and linear rate increase of the subsidence reached approximately -196 mm and -44 mm/yr, respectively, during the period of this study. Besides the subsidence rate changes, the earthquake also affected the expansion of the localized subsiding areas at several sites. The earthquake-activated fault affected the ground surface of the surrounding area, moving east and subsiding in the western part of the study area. Meanwhile, variations of the nonlinear subsidence to the seasonal precipitation depended on the aquifer system behavior to retain an elastic expansion and land cover types in the investigated regions.